2021
DOI: 10.1007/s00784-020-03622-9
|View full text |Cite|
|
Sign up to set email alerts
|

How is neck dissection performed in Oral and Maxillofacial Surgery? Results of a representative nationwide survey among university and non-university hospitals in Germany

Abstract: Introduction Neck dissection (ND) is a surgical procedure addressing cervical lymph nodes and metastases in patients with oral squamous cell carcinoma (OSCC). The aim of this study was to analyze clinical decisions regarding indications and variations of ND in Oral and Maxillofacial Surgery (OMFS) in Germany. Material and methods A nationwide survey of the German Association of Oral and Maxillofacial Surgery was performed using dynamic online quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…However, its extension to levels further caudally with the preservation of important nonlymphatic structures, in terms of a CND in cases with preoperative evidence of LNMs, remains controversial, with unpredictable outcomes [ 21 ]. A nationwide survey of the German Association of Oral and Maxillofacial Surgery reported that 69.74% of participating hospitals included neck levels IV and V in patients with node-positive necks [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, its extension to levels further caudally with the preservation of important nonlymphatic structures, in terms of a CND in cases with preoperative evidence of LNMs, remains controversial, with unpredictable outcomes [ 21 ]. A nationwide survey of the German Association of Oral and Maxillofacial Surgery reported that 69.74% of participating hospitals included neck levels IV and V in patients with node-positive necks [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] The authors endorse the view that prophylactic neck dissections are warranted for clinically negative head and neck tumors that have a significant probability of having occult metastasis in the neck. [44][45][46] In the case of large tumours mandating microsurgical reconstruction, as the ones described in this series, the authors do not regularly perform sentinel node biopsy, due to the risk of overlooking skip metastases. 44 More than 80% of patients presented an eventful postoperative period.…”
Section: Discussionmentioning
confidence: 99%
“…[44][45][46] In the case of large tumours mandating microsurgical reconstruction, as the ones described in this series, the authors do not regularly perform sentinel node biopsy, due to the risk of overlooking skip metastases. 44 More than 80% of patients presented an eventful postoperative period. Flap partial and total necrosis only occurred in seven (6.1%) and four (3.5%) cases, respectively.…”
Section: Discussionmentioning
confidence: 99%